Book Review: A Lcs Chan Reader. Pioneering Essays on Biblical and Asian Theological Ethics - Bismoko Mahamboro (P3TK, Sanata Dharma University, 2019)
This book is a rare book which is an anthology written by Lcs Chan,an Asian moral theologian.